ANALISIS PERBANDINGAN NILAI PROFIT PENGGUNAAN LAHAN PERTANIAN DAN PERTAMBANGAN PASIR DI DESA PEGIRINGAN KECAMATAN BANTARBOLANG KABUPATEN PEMALANG - Is One Nugroho; Sriyono Sriyono; Hariyanto Hariyanto (Geo-Image, 2017)
Change use of agricultural land into mining sand land show has been a change of land use activity. The purpose of this study, 1) Knowing the change use of agricultural land into mining sand land, 2) Knowing the factor driving change use of agricultural land into mining sand land, 3) Knowing the ratio of the value profit of agricultural land use and mining sand land, 4) Knowing activity farmer after the change use of agricultural land into sand mining land. Data analysis use descriptive percentage analysis and interpretation Quickbird Citra. The result show change in land use as a result of a rental system of agricultural land owned farmer by Paguyuban Anugerah for use as a commercial sand mining, average cost rental 21.000 rupiah to meter square. The driving factor that farmer lease their land, costs, land does not have irrigation canals, and land surface conditions. Value profit land use mining sand is more profitable, there is only one drawback to the use of mining sand land are damaged land surface conditions so require post mining reclamation. Farmer do not do mining sand activity after the change use of agricultural land.